Management of Religious Activities in Improving Students’ Akhlakul Karimah - Ilham Sumalee; Hayumuti; Athia Nur Kamilah (NAJAHA, 2025)
This study aims to describe and understand the management of religious activities in enhancing students' moral character in the Muslim Santitham Foundation School, Thailand. This research uses a qualitative descriptive method obtained through observation, interviews, scientific journal literature, and books. The data analysis technique uses data reduction, data display, and conclusion. The results of this study indicate that the management of religious activities in enhancing the moral character of students in the Muslim Santitham Foundation School Thailand is reflected in activities such as congregational Dhuha prayer, religious lectures from foreign religious teachers, and reading short surahs/dhikr. The implementation of these activities is supported by methods of example, habituation, and practice.